Renal functions in patients with metabolic syndrome - Asha Augusthy; Suchanda Sahu; Ashok Kumar Jeppu; Seema Jawalekar (International Journal of Medical Research and Review, 2018)
Introduction: Metabolic syndrome consists of a constellation of metabolic abnormalities that confer increased risk of diabetes mellitus. The aim of the present study was to study renal functions in patients with metabolic syndrome.Materials and methods: 50 controls and 50 individuals with metabolic syndrome were selected by purposive sampling technique. Waist circumference and blood pressure was measured and serum levels of fasting blood sugar, triglycerides and HDL were estimated and eGFR was calculated in controls and cases.Results: We found that serum urea andcreatininelevels were significantly increased andeGFR levels were significantly decreased in metabolic syndrome when compared to controls.Conclusion: Our study concluded that there is significant renal dysfunction in patients with metabolic syndrome.